Me, myself & Irene - Thomas, Bradley; Farrelly, Bobby; Farrelly, Bobby; Farrelly, Bobby; Farrelly, Peter; Farrelly, Peter; Farrelly, Peter; Cerrone, Mike; Carrey, Jim 1962- (Twentieth Century Fox Home Entertainment, 2000)
Rhode Island state trooper Charlie Baileygates proves that nice guys finish first after marrying the prettiest gal in town. But when she leaves him for another man Charlie develops a split personality, and his outrageous opposite, Hank, is born!